Exploiting natural antiviral immunity for the control of pandemics: Lessons from Covid-19. (February 2022) - Aricò, Eleonora; Bracci, Laura; Castiello, Luciano; Urbani, Francesca; Casanova, Jean-Laurent; Belardelli, Filippo
Abstract: The outbreak of coronavirus disease 2019 (COVID-19), triggered by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), and the disruptive global consequences in terms of mortality and social and economic crises, have taught lessons that may help define strategies to better face future pandemics. Innate and intrinsic immunity form the front-line natural antiviral defense. They involve both tissue-resident and circulating cells, which can produce anti-viral molecules shortly after viral infection. Prototypes of these factors are type I interferons (IFN), antiviral cytokines with a long record of clinical use. During the last two years, there has been an impressive progress in understanding the mechanisms of both SARS-CoV-2 infection and the cellular and soluble antiviral responses occurring early after viral exposure. However, this information was not sufficiently translated into therapeutic approaches. Insufficient type I IFN activity probably accounts for disease progression in many patients. This results from both the multiple interfering mechanisms developed by SARS-CoV-2 to decrease type I IFN response and various pre-existing human deficits of type I IFN activity, inherited or auto-immune. Emerging data suggest that IFN-I-mediated boosting of patients' immunity, achieved directly through the exogenous administration of IFN-β early post viral infection, or indirectly following inoculation of heterologous vaccines (e.g., Bacillus Calmette Guerin), might play a role against SARS-CoV-2. We review how recent insights on the viral and human determinants of critical COVID-19 pneumonia can foster clinical studies of IFN therapy. We also discuss how early therapeutic use of IFN-β and prophylactic campaigns with live attenuated vaccines might prevent a first wave of new pandemic viruses. Highlights: COVID-19 experience calls global attempts to exploit knowledge on innate antiviral immunity for future pandemics. IFN-β plays an early protective role in Sars-COV-2 infection and can mitigate disease progression. LAV and agents fostering innate immunity, including IFN-β, may represent first-line strategy for controlling viral pandemics. Clinical trials with IFN-β in COVID-19 patients should include personalized therapies based on novel biomarkers. Research on mechanisms of antiviral innate immunity should be encouraged for its potential impact on public health prevention strategies.